Peripheral arterial stiffness is associated with maximal oxygen uptake in athletes - Hashimoto, Y.; Okamoto, T. (International Journal of Sports Medicine, 2023)
Increased central arterial stiffness is associated with decreased maximal oxygen uptake (VO2max). Endurance exercise training improves arterial function throughout the whole body, but the relationship between central and peripheral arterial stiffness and VO2max is unknown. The present study investigated the relationship between central and peripheral arterial stiffness and VO2max in endurance-trained athletes. Twenty-one young male endurance-trained athletes and 12 sedentary controls were included in this study. Resting values for carotid-femoral velocity and femoral-ankle pulse wave velocity were obtained to assess central and peripheral arterial stiffness, respectively. VO2max was obtained by incremental cycle ergometer testing. Both carotid-femoral pulse wave velocity (P=0.019) and femoral-ankle pulse wave velocity (P=0.028) were lower in athletes than in controls. VO2max was significantly higher in athletes compared to controls (P<0.001). Significant correlations were found between carotid-femoral pulse wave velocity and VO2max (r=-0.510, P=0.018) and between femoral-ankle pulse wave velocity and VO2max (r=-0.472, P=0.031) in athletes. However, no correlations were evident in controls. These results suggest that higher VO2max is associated with lower peripheral arterial stiffness in addition to central arterial stiffness among endurance-trained athletes.